Evaluation of Corn Fodder Hydroponic Nutrient Content As a Substitute of Forgive Livestock Feed - Sri Widiastuti; Nur Achmad Purnama Nugraha; Diah Mustika Rani; Tri Puji Rahayu (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
Hydroponic fodder is a forage that is cultivated hydroponically. Fodder hydroponic cultivation can be done only with liquid media, carried out in a controlled environment, and a short planting period. Wheat, barley, sorghum, and corn are cereal crops that can be cultivated hydroponically as animal feed. Corn is a cereal crop that is easily available in Indonesia. Corn seeds grown hydroponically will affect the nutrient content. The purpose of this study was to determine the nutrient content of corn fodder. This research uses literature study and experimental methods. Data analysis used descriptive analysis. Based on the proximate analysis of corn fodder, the crude protein content was 11.135%, crude fat content was 4.950%, ash content was 2.340%, crude fiber content was 15.210%, water content was 88.99%, Ca content was 0.440%, crude fiber content was 0.440%. P was 0.770%, NaCl content was 0.036%, Na content was 0.014%, and ME was 31.200 MJ/kg. In conclusion, this corn fodder can be used as a forage substitute for animal feed because it has a fairly good nutrient content.